From the Schematism to the Typic. How Can We Be moral? - Scaglia, Lara (Con-Textos Kantianos. International Journal of Philosophy, 2021)
Kant’s chapter “On the Typic of the Pure Practical Power of Judgement” is one of the most obscure passages of the Critique of Practical Reason and it has often been regarded as a mere appendix. However, it deals with a fundamental question, namely, how can the pure practical law be applied to particular cases. In this paper, I would like to make an original contribution towards a better understanding of this chapter by comparing it to the Schematism chapter on the basis of their analogical relation and suggesting how the reference to a sensus communis could help in solving the (unsolved) aim of the Typic chapter.
Keywords: Typic; analogy; schema; common sense